Pastor's role in human development and its implications on Parish life and ministry the case of UP Diliman Community, Philippines - Athapha, Francis 1955- (1994)
A descriptive method of research was used in examining the role of a pastor in his parish in the light of various realities prevailing. It was concluded that it is still an accepted fact that the people believe that the main role of a pastor in relation to teaching is to communicate the Word of God in a salvation-centered message and in a Bible-based manner. The pastor also has teaching, preaching, healing, organizational and feeding function or ministries. Also, the pastor is seen as a catalyst and agent of change in the community. He is expected to lead the people improve the quality of their lives.